2021
DOI: 10.3390/ani11092668
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Soybean Varieties and Heat Treatments and Its Effect on Growth Performance and Nutrient Digestibility in Broiler Chickens

Abstract: As production of European soybeans is expected to grow, optimal processing conditions need to be ensured for small and heterogeneous batches of soybeans. The effect of different soybean varieties, as well as heat treatments, on the growth performance and nutrient digestibility in broiler chickens was investigated. Two varieties, regarded as heat stable and heat labile after preliminary experiments, were partially de-oiled and thermally processed at 110 °C for 20 min and 120 °C for 20 min. The resulting soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Therefore, in food, feed and industrial applications, several simple indices, including NSI, PDI, PS‐KOH, and others, have been selectively measured for assessing both nutritional values and functional properties of protein products (Averina et al, 2021; Batal et al, 2000; Frikha et al, 2012; Jia et al, 2021; Parsons, 1996; Shen et al, 2021; van Eys & Ruiz, 2021; Wolf et al, 1971). In contrast, TIA is not commonly measured, even though it is the most reliable quality parameter (Frikha et al, 2012; Hemetsberger et al, 2021; McNaughton et al, 1981; Qin et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in food, feed and industrial applications, several simple indices, including NSI, PDI, PS‐KOH, and others, have been selectively measured for assessing both nutritional values and functional properties of protein products (Averina et al, 2021; Batal et al, 2000; Frikha et al, 2012; Jia et al, 2021; Parsons, 1996; Shen et al, 2021; van Eys & Ruiz, 2021; Wolf et al, 1971). In contrast, TIA is not commonly measured, even though it is the most reliable quality parameter (Frikha et al, 2012; Hemetsberger et al, 2021; McNaughton et al, 1981; Qin et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The method for measuring trypsin inhibitor activity (TIA) has been improved in simplicity, accuracy, and standardization (AOCS, 2021; Kakade et al, 1974; Liu, 2019). Although TIA is the most reliable index for protein quality and subsequent animal performance (Frikha et al, 2012; Hemetsberger et al, 2021; Liu & Ruiz, 2021; McNaughton et al, 1981; Qin et al, 1996), it has been more practical and popular to measure PDI, NSI, UA and/or PS‐KOH for soybeans and other protein products (Averina et al, 2021; Cho & Ryu, 2021; Hemetsberger et al, 2021; Ibáñez et al, 2020; Jia et al, 2021; Parsons, 1996; Ruiz et al, 2020; van Eys & Ruiz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The observed differences in crude nutrient compositions between the diets arose from the different soybean varieties and exerted some potential influence on gut microbiota. A detailed description of diets on performance indices is given in Hemetsberger et al (2021). The starch, fat, fiber, and mineral contents of feedstuff are known for their ability to shift the microbial composition in the gastrointestinal tract [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The heat-labile variety caused an increase in two Peptostreptococcaceae, one Clostridiaceae and one Lactobacillaceae. A correlation analysis of selected parameters received from Hemetsberger et al (2021) with ASVs found in the ileal and cecal digesta is shown in Figures S1 and S2 in the Supplementary Materials. Used phenotypical parameters were apparent ileal crude protein and amino acid digestibility, nitrogen retention, apparent total tract starch digestibility, weight gain and feed efficiency.…”
Section: Or Peer Review 9 Of 15mentioning
confidence: 99%
See 1 more Smart Citation